María Mariño in the Galicien literary system. Critics reflections - Rodríguez González, Olivia (Madrygal. Revista de Estudios Gallegos, 2025)
Reflections on how the criticism works in the Galicien literary system with regard to Maria Mariño´s canonizationclaim, an author to whom was dedicated the 2007 Galicien Letters Day